EPDM (Ethylene-Propylene-Diene Monomer) foaming material with low odor and high mechanical property and preparation method thereof
By combining PVA/SiO2 composite wrapping citric acid-sodium bicarbonate foaming agent with OBSH, the cell structure and mechanical properties of ethylene propylene ternary rubber (EPDM) foam material are optimized, and the shortcomings of existing materials in environmental protection, storage stability and mechanical properties are solved, and high-performance EPDM foam material with low VOC emissions and low cost are achieved.
Patent Information
- Application Number
- CN202510189973.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-20
AI Technical Summary
The existing ethylene propylene ternary rubber (EPDM) foam materials have problems such as insufficient environmental protection, poor cell structure control and limited mechanical properties, especially in terms of VOC emissions, storage stability and mechanical properties.
The PVA/SiO2 composite wrapping of citric acid-sodium bicarbonate foaming agent is used to combine with OBSH to form a binary foaming system (CO2+N2), optimize the cell structure, improve the material's resistance to compression and deformation, and improve the dispersion and decomposition temperature of the foaming agent by adjusting the mesh number and surface modification of sodium bicarbonate.
It has achieved low VOC emission, low odor and low cost EPDM foaming material, with excellent mechanical properties, good cell structure stability and improved storage stability, and is suitable for automobiles, rail transit and other industrial applications.
Smart Images

Figure CN119875251A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer materials, and specifically relates to a method for preparing an environmentally friendly foaming agent. Based on the method, an ethylene propylene diene monomer (EPDM) foaming material with low cost, low odor, low VOC emission and excellent mechanical properties and a preparation method thereof are developed. Background Art
[0002] Ethylene propylene diene monomer (EPDM) foam is widely used in seals, sound insulation and pressure-resistant cushions that are exposed to harsh environments for a long time due to its excellent weather resistance, heat resistance, ozone resistance and elasticity. However, the current EPDM foam materials still have the following problems: the environmental friendliness of traditional foaming agents is insufficient. Many foaming agents (such as azo foaming agents AC and OBSH) may release toxic volatile organic compounds (VOCs), which do not comply with modern environmental regulations; the pore structure is not well controlled. The conventional sodium bicarbonate-citric acid system releases gas too quickly, resulting in uneven pore size, which affects the mechanical properties of the foam; the mechanical properties are limited. While the existing environmentally friendly EPDM foam improves environmental friendliness, it often leads to a decrease in the mechanical properties of the material due to uneven pores or improper control of the foaming ratio, such as insufficient tensile strength, tear strength and wear resistance; the storage stability is poor. Some inorganic foaming agents have strong hygroscopicity, which may cause failure or uneven foaming after long-term storage. Therefore, there is an urgent need for an environmentally friendly, low-VOC, high-mechanical-performance EPDM foam material to meet the needs of automotive, rail transit and other industrial applications. Summary of the invention
[0003] The purpose of the present invention is to provide a low-cost, low-odor, low-VOC emission and excellent mechanical properties of ethylene propylene diene monomer (EPDM) foaming material and a preparation method thereof. The present invention adopts PVA / SiO2 composite to wrap the citric acid-sodium bicarbonate foaming agent to achieve slow release control, prevent premature decomposition, improve storage stability, and combine with OBSH compounding to form a binary foaming system (CO2+N2), optimize the pore structure, improve the material's resistance to compression deformation, and reduce VOC emissions.
[0004] To achieve the above object, the present invention adopts the following technical solution: The invention discloses an EPDM rubber foaming material with low odor and high mechanical properties. The raw materials used in the foaming material include, by weight, 100 parts of EPDM rubber, 6 parts of carbon black, 40 parts of light calcium carbonate, 15 parts of paraffin oil, 10 parts of zinc oxide, 1 part of vulcanizing agent, 1.5 parts of accelerator, 2 parts of stearic acid, 1 part of lubricant and 10 parts of foaming agent.
[0005] In the present invention, the EPDM rubber (EPDM) can be selected from environmentally friendly raw rubbers, including Lanxess Keltan Eco5470, ExxonMobil Vistalon 2504 Eco, Dow Chemical Nordel IP 3430 Bio and South Korea Kumho Petrochemical Kumho KEP 460 Bio. These EPDM rubbers are mainly composed of bio-based raw materials (about 70% of which are made by converting sugarcane ethylene) and have excellent environmental protection properties and a low carbon footprint. Among them, Keltan Eco 5470 has both high performance and environmental protection advantages, and is particularly suitable for environmentally friendly sealing strips, automotive parts and industrial rubber products. In addition, the ethylidene norbornene (ENB) content of these EPDM rubbers is less than 5%, which can effectively reduce the odor volatilization during the foaming process and during the use of the product while ensuring a good vulcanization speed, further meeting the requirements of environmental protection and low pollution.
[0006] In the present invention, the carbon black can be selected from Orion NEROX 505, NEROX 510, Cabot BlackPearls 800, Degussa Special Black 550, all of which have good dispersibility, stability and environmental performance. The preferred NEROX 505 has the characteristics of small particle size (4 nm), low sulfur content, low VOC emission, etc., which can reduce the release of pollutants from rubber materials and comply with environmental regulations (such as RoHS and REACH). In the present invention, the carbon black has a BET specific surface area of 50-150 m² / g, a pH value of 6-9, a carbon content of ≥95%, a dispersibility of ≥90%, and is prepared by a clean furnace method to reduce the emission of harmful substances and improve the environmental performance of the product.
[0007] In the present invention, the paraffin oil is preferably SK YUBASE 8, American Sun Sanepar 936, Sunpar 2280, and Nytex 4700. These environmentally friendly paraffin oils have a saturated hydrocarbon content of ≥90%, an aromatic hydrocarbon content of ≤1%, a kinematic viscosity of 10-50 cSt at 40°C, a kinematic viscosity of 2-8 cSt at 100°C, a flash point of ≥200°C, a pour point of ≤-10°C, low VOC emissions, and a low sulfur content (≤10 ppm), comply with REACH regulations or FDA standards, and can ensure the environmental safety and long-term stability of rubber products.
[0008] In the present invention, zinc oxide acts as a heat stabilizer and an activator.
[0009] In the present invention, the vulcanizing agent includes any one of sulfur, zinc dibenzyl dithiocarbamate, dibenzoyl peroxide, dicumyl peroxide and the like.
[0010] In the present invention, the accelerator comprises zinc dibenzyl dithiocarbamate (ZBEC) and / or tetrabenzyl thiuram disulfide (TBZTD), preferably a mixture of zinc dibenzyl dithiocarbamate and tetrabenzyl thiuram disulfide.
[0011] In the present invention, the lubricant is polyethylene glycol.
[0012] In the present invention, the foaming agent is a mixture of 4,4'-oxybisbenzenesulfonylhydrazine (OBSH) and modified sodium bicarbonate, and the mass ratio of the two is 1:(1-3). The mixed gas generated by OBSH and modified sodium bicarbonate is a mixture of N2 and CO2, which can optimize the foaming uniformity, improve the stability of the pore structure of the material, and reduce the amount of OBSH while ensuring that the shrinkage rate of the foaming material is less than 10%, thereby reducing the cost and better maintaining the environmental protection performance.
[0013] In the present invention, the preparation method of the modified sodium bicarbonate comprises the following steps: (a) 5 g of PVA was dissolved in 100 mL of water, heated to 80 °C, stirred for 2 h, then 10 g of citric acid was added, stirred evenly, and then 10 g of NaHCO3 (100 mesh to 500 mesh) was slowly added, stirred for 30 min, and then dried in an oven at 80 °C to obtain PVA-coated citric acid-NaHCO3 particles; (b) 2 g of SiO2 nanopowder was dispersed in 50 mL of 50% ethanol solution, and ultrasonicated for 30 min. Then, the PVA-coated citric acid-NaHCO3 particles prepared in step (a) were added, stirred for 1 h, and then centrifuged at 8000 rpm for 10 min. The particles were collected and dried. (c) Take 1 g of KH-550 and add it to 100 mL of anhydrous ethanol, stir evenly, add the particles prepared in step (b), and disperse them evenly in the solution, stir at room temperature for 1 h, and dry at 50°C for 12 h.
[0014] In the present invention, by adjusting the mesh size of sodium bicarbonate (100-500 mesh) in the foaming agent, its dispersibility in the rubber matrix can be improved, thereby improving the mechanical properties of the EPDM foaming material. At the same time, sodium bicarbonate is surface-modified with citric acid to increase its decomposition temperature, making it more consistent with the foaming curve of rubber, and can improve its dispersibility in the formula and reduce the problem of cell shrinkage. The surface of sodium bicarbonate is coated with a composite layer of polyvinyl alcohol (PVA) and SiO2, which can make it more stable when thermally decomposed during the foaming process and release gas more uniformly, thereby optimizing the foaming structure of EPDM and improving the resilience and dimensional stability of the foaming material. In addition, the present invention can improve the interfacial compatibility between the filler and the rubber matrix through the silane coupling agent-modified silicon powder and the PVA-wrapped citric acid-sodium bicarbonate, while improving the processing performance of the material and reducing the volatile organic compound (VOC) emissions that may be generated during the foaming process, so that the EPDM foam material is superior to the existing technology in terms of environmental protection, mechanical properties and durability, and has broad application prospects, including high-performance seals, shock-absorbing materials and lightweight high-strength elastomers.
[0015] The preparation method of the EPDM rubber foam material comprises the following steps: 1) Add EPDM, carbon black, light calcium carbonate, zinc oxide, lubricant, stearic acid and half of the paraffin oil into a mixer for mixing once to make the materials evenly dispersed, and then thinly slice to obtain the first stage rubber compound; 2) Add the first-stage rubber material, accelerator, vulcanizer, foaming agent and remaining paraffin oil into a mixer for secondary mixing, so that the materials are mixed evenly and then thinly sliced to obtain a mixed rubber material; 3) The mixed rubber material is sequentially subjected to extrusion, primary vulcanization, and secondary vulcanization to finally obtain the EPDM rubber foam material.
[0016] In the present invention, the temperature of the first mixing is 90-110° C., and the time is 10-12 min; the temperature of the thin sheet is 30-50° C., and the sheet thickness is 1-3 mm.
[0017] In the present invention, the temperature of the secondary mixing is 60-90° C., and the time is 2-5 min; the temperature of the thin through-sheet is 80-100° C., and the sheet thickness is 2-4 mm.
[0018] In the present invention, the extrusion temperature is 100-120°C.
[0019] In the present invention, the primary vulcanization temperature is 130-135°C and the time is 20-30 min. The primary vulcanization temperature is low, so that OBSH is decomposed, the colloid expands to a certain extent, the hardness is reduced, the volume is increased, and the colloid has a certain degree of cross-linking, has sufficient strength to support the pores, and improves the anti-shrinkage performance.
[0020] In the present invention, the temperature of the secondary vulcanization is 150-155°C, preferably 151-154°C, and more preferably 152-153°C; the time of the secondary vulcanization is 10-30 min, preferably 12-28 min, and more preferably 15-25 min.
[0021] In the present invention, the synthesized foaming agent is fully decomposed through the secondary vulcanization process, the colloid volume is further increased, and the internal structure of the EPDM foaming material is optimized. At the same time, after the EPDM product reaches a certain degree of vulcanization, even if it is not continuously heated, it can still continue to undergo deep vulcanization reaction under the action of residual heat or during storage, and even further cross-link under dynamic load conditions. Therefore, the main purpose of secondary vulcanization is to promote further cross-linking of EPDM products, significantly improve their mechanical properties, reduce the compression permanent deformation rate, thereby enhancing their long-term use stability and durability, and making their application advantages in the fields of high-performance seals, shock-absorbing materials and weather-resistant elastomers more prominent.
[0022] The EPDM rubber foam material provided by the invention can be applied to the fields of automobiles, rail transportation, etc.
[0023] The beneficial effects of the present invention are: (1) Low cost and excellent mechanical properties: The present invention can bring about a more uniform foaming effect in EPDM by optimizing the mesh size of sodium bicarbonate, thereby improving its mechanical properties, elasticity, processing properties, and thermal insulation and sound insulation properties. The fine pore structure and stable foaming effect have a significant effect on improving the comprehensive performance and application performance of EPDM. At the same time, the PVA / SiO2 composite coating technology can effectively control the foaming process and improve the material's resistance to compression deformation. In addition, by compounding the PVA / SiO2 composite-wrapped citric acid-sodium bicarbonate foaming agent with OBSH to effectively improve the dispersibility of the foaming agent in the EPDM matrix, the problem of pore shrinkage and unevenness of the traditional sodium carbonate foaming agent is solved.
[0024] (2) Low VOC emissions, in compliance with environmental regulations: The present invention optimizes the rubber formula and uses low VOC emission raw materials, effectively reducing the VOC emission of EPDM foaming materials, in compliance with the requirements of China's "Law of the People's Republic of China on the Prevention and Control of Environmental Pollution by Solid Wastes" and the EU REACH and RoHS environmental regulations. The use of microcapsule foaming agents modified with silane coupling agents reduces the use of traditional azo foaming agents and further reduces the emission of volatile organic compounds.
[0025] (3) Low odor and excellent environmental performance: The use of high-purity PVA and SiO2 nano-coating not only optimizes the release rate of the foaming agent, but also effectively reduces the irritating gases that may be produced during the foaming process, making the odor level of the EPDM foaming material less than 2.5 at room temperature and ≤ 3.5 when heated in a water bath at 80°C. TBZTD and ZBEC are used as accelerators to avoid the production of nitrosamines and improve environmental performance. Carbon black uses NEROX 505 with a smaller specific surface area to reduce the surface oxygen-containing functional groups, improve the anti-fouling performance and long-term use performance of the material. Paraffin oil uses YUBASE8, which has a flash point higher than 260°C and a low aromatic group content, reducing odor residue.
[0026] (4) A binary foaming system (CO2+N2) is used to regulate the cell distribution and improve the cell uniformity. The present invention significantly reduces the cell collapse and local cell oversize problems by compounding the citric acid-sodium bicarbonate foaming agent with OBSH by PVA / SiO2 composite wrapping, thereby improving the mechanical properties of the EPDM rubber foaming material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The DTA curves of sodium bicarbonate and the PVA / SiO2 composite wrapped citric acid-sodium bicarbonate prepared in Example 1. As can be seen from the figure, the decomposition temperature of the modified sodium bicarbonate is increased from the original value to a range more suitable for rubber foaming (150-170°C), and the decomposition range is significantly reduced, which makes it better match the EPDM vulcanization and foaming curves and improves the stability of the pore structure.
[0028] Figure 2 The optical microscope images of EPDM foamed materials prepared by using the foaming agents of Example 1 (a) and Comparative Examples 5 to 9 (be) are shown in the figure. As can be seen from the figure, as the particle size of sodium bicarbonate decreases, the pore size of the EPDM foamed material gradually decreases, and at the same time, the distribution of the pores becomes more uniform, the number of white spots is significantly reduced, and the dispersibility is significantly improved. This shows that optimizing the particle size of the coated and modified sodium bicarbonate can effectively improve the dispersibility of the foaming agent, thereby enhancing the uniformity of the pore structure and improving the overall performance of the material.
[0029] Figure 3 The thermogravimetric curve of the EPDM foam material prepared by using the foaming agent of Example 1. As can be seen from the figure, the prepared EPDM foam material has high thermal stability, which helps to improve the heat resistance and flame retardancy of the product during long-term use. DETAILED DESCRIPTION
[0030] A low-odor, high-mechanical-performance EPDM foaming material, wherein the raw materials used include, by weight: 100 parts of EPDM, 6 parts of carbon black, 40 parts of modified sodium bicarbonate, 15 parts of paraffin oil, 10 parts of zinc oxide, 1 part of vulcanizing agent, 1.5 parts of accelerator, 2 parts of stearic acid, 1 part of lubricant, and 10 parts of foaming agent. The preparation method thereof comprises the following steps: 1) Add EPDM, carbon black, light calcium carbonate, zinc oxide, lubricant, stearic acid and half of the paraffin oil into a mixer, mix at 90-110°C for 10-12 min to evenly disperse the materials, and then thinly slice at 30-50°C to obtain the first-stage rubber compound with a thickness of 1-3 mm; 2) Add the first-stage rubber, accelerator, vulcanizer, foaming agent and remaining paraffin oil into a mixer, and mix them for a second time at 60-90°C for 2-5 min. After the materials are mixed evenly, thin sheets are formed at 80-100°C to obtain a mixed rubber with a thickness of 2-4 mm. 3) The mixed rubber material is extruded at 100-120°C, vulcanized at 130-135°C for 20-30 min, and vulcanized at 150-155°C for 10-30 min, to finally obtain the EPDM rubber foam material.
[0031] Wherein, the foaming agent is a mixture of 4,4'-oxybisbenzenesulfonylhydrazine (OBSH) and modified sodium bicarbonate in a mass ratio of 1:(1-3).
[0032] The preparation method of the modified sodium bicarbonate comprises the following steps: (a) 5 g of PVA was dissolved in 100 mL of water, heated to 80 °C, stirred for 2 h, then 10 g of citric acid was added, stirred evenly, and then 10 g of NaHCO3 (100 mesh to 500 mesh) was slowly added, stirred for 30 min, and then dried in an oven at 80 °C to obtain PVA-coated citric acid-NaHCO3 particles; (b) 2 g of SiO2 nanopowder was dispersed in 50 mL of 50% ethanol solution, and ultrasonicated for 30 min. Then, the PVA-coated citric acid-NaHCO3 particles prepared in step (a) were added, stirred for 1 h, and then centrifuged at 8000 rpm for 10 min. The particles were collected and dried. (c) Take 1 g of KH-550 and add it to 100 mL of anhydrous ethanol, stir evenly, add the particles prepared in step (b), and disperse them evenly in the solution, stir at room temperature for 1 h, and dry at 50°C for 12 h.
[0033] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0034] In the embodiment, the EPDM rubber is selected from LANXESS Keltan Eco 5470. The carbon black is selected from Orion NEROX505. The paraffin oil is selected from SK YUBASE 8. The vulcanizing agent is selected from sulfur. The accelerator is selected from a mixture of zinc dibenzyl dithiocarbamate and tetrabenzyl thiuram disulfide in a mass ratio of 1:1. The lubricant is selected from polyethylene glycol 2000.
[0035] Example 1 Preparation of foaming agent 1) Dissolve 5 g PVA in 100 mL water, heat to 80 °C, stir for 2 h, then add 10 g citric acid, stir evenly, then slowly add 10 g NaHCO3 (500 mesh), continue stirring for 30 min, and then dry in an oven at 80 °C to obtain PVA-coated citric acid-NaHCO3 particles; 2) Disperse 2 g of SiO2 nanopowder in 50 mL of 50% ethanol solution, sonicate for 30 min, then add the PVA-coated citric acid-NaHCO3 particles prepared in step (a), stir for 1 h, centrifuge at 8000 rpm for 10 min, collect the particles and dry them; 3) Take 1g KH-550 and add it to 100mL anhydrous ethanol, stir evenly, add the particles prepared in step (b), and disperse them evenly in the solution, stir at room temperature for 1h, and dry at 50℃ for 12h to obtain PVA / SiO2 composite coated with citric acid-sodium bicarbonate; 4) According to weight, 5 parts of PVA / SiO2 composite-encapsulated citric acid-sodium bicarbonate and 5 parts of 4,4'-oxybisbenzenesulfonyl hydrazide were mixed evenly to prepare a foaming agent, which was marked as foaming agent A.
[0036] Example 2 Preparation of foaming agent 1) Take 5g PVA and dissolve it in 100mL water, heat it to 80℃, stir it for 2h, then add 10g citric acid, stir it evenly, then slowly add 10g NaHCO3 (500 mesh), continue stirring for 30min, and then dry it in an oven at 80℃ to obtain PVA-coated citric acid-NaHCO3 particles; 2) Disperse 2 g of SiO2 nanopowder in 50 mL of 50% ethanol solution, sonicate for 30 min, then add the PVA-coated citric acid-NaHCO3 particles prepared in step (a), stir for 1 h, centrifuge at 8000 rpm for 10 min, collect the particles and dry them; 3) Take 1g KH-550 and add it to 100mL anhydrous ethanol, stir evenly, add the particles prepared in step (b), and disperse them evenly in the solution, stir at room temperature for 1h, and dry at 50℃ for 12h to obtain PVA / SiO2 composite coated with citric acid-sodium bicarbonate; 4) According to weight, 7 parts of PVA / SiO2 composite coated citric acid-sodium bicarbonate and 5 parts of 4,4'-oxybisbenzenesulfonyl hydrazide are prepared into a foaming agent, which is marked as foaming agent B.
[0037] Example 3 Preparation of foaming agent 1) Take 5g PVA and dissolve it in 100mL water, heat it to 80℃, stir it for 2h, then add 10g citric acid, stir it evenly, then slowly add 10g NaHCO3 (500 mesh), continue stirring for 30min, and then dry it in an oven at 80℃ to obtain PVA-coated citric acid-NaHCO3 particles; 2) Disperse 2 g of SiO2 nanopowder in 50 mL of 50% ethanol solution, sonicate for 30 min, then add the PVA-coated citric acid-NaHCO3 particles prepared in step (a), stir for 1 h, centrifuge at 8000 rpm for 10 min, collect the particles and dry them; 3) Take 1g KH-550 and add it to 100mL anhydrous ethanol, stir evenly, add the particles prepared in step (b), and disperse them evenly in the solution, stir at room temperature for 1h, and dry at 50℃ for 12h to obtain PVA / SiO2 composite coated with citric acid-sodium bicarbonate; 4) According to weight, 10 parts of PVA / SiO2 composite coated citric acid-sodium bicarbonate and 5 parts of 4,4'-oxybisbenzenesulfonyl hydrazide are prepared into a foaming agent, which is marked as foaming agent C.
[0038] Comparative Example 1 OBSH Take 4,4'-oxybisbenzenesulfonylhydrazide as a blowing agent and mark it as blowing agent D.
[0039] Comparative Example 2 PVA / SiO2 composite wrapped sodium bicarbonate without citric acid 1) Dissolve 5 g of PVA in 100 mL of water, heat to 80 °C, stir for 2 h, then slowly add 10 g of NaHCO3 (500 mesh), continue stirring for 30 min, and then dry in an oven at 80 °C to obtain PVA-coated NaHCO3 particles; 2) Disperse 2 g of SiO2 nanopowder in 50 mL of 50% ethanol solution, sonicate for 30 min, then add the PVA-coated NaHCO3 particles prepared in step (a), stir for 1 h, centrifuge at 8000 rpm for 10 min, collect the particles and dry them; 3) Take 1g KH-550 and add it to 100mL anhydrous ethanol, stir evenly, add the particles prepared in step (b), and disperse them evenly in the solution, stir at room temperature for 1h, and dry at 50℃ for 12h to obtain PVA / SiO2 composite coated sodium bicarbonate; 4) According to weight, 5 parts of PVA / SiO2 composite-encapsulated sodium bicarbonate and 5 parts of 4,4'-oxybisbenzenesulfonyl hydrazide are mixed to form a foaming agent, which is marked as foaming agent E.
[0040] Comparative Example 3: PVA / SiO2 composite coated with citric acid-sodium bicarbonate without silane modification 1) Take 5g PVA and dissolve it in 100mL water, heat it to 80℃, stir it for 2h, then add 10g citric acid, stir it evenly, then slowly add 10g NaHCO3 (500 mesh), continue stirring for 30min, and then dry it in an oven at 80℃ to obtain PVA-coated citric acid-NaHCO3 particles; 2) Disperse 2 g of SiO2 nanopowder in 50 mL of 50% ethanol solution, ultrasonicate for 30 min, then add the PVA-coated citric acid-NaHCO3 particles prepared in step (a), stir for 1 h, centrifuge at 8000 rpm for 10 min, collect the particles and dry them to obtain PVA / SiO2 composite-coated citric acid-sodium bicarbonate without silane modification; 3) According to weight, 5 parts of PVA / SiO2 composite coated with citric acid-sodium bicarbonate without silane modification and 5 parts of 4,4'-oxybisbenzenesulfonyl hydrazide were prepared into a foaming agent, which was marked as foaming agent F.
[0041] Comparative Example 4: Mixture of citric acid and sodium bicarbonate 1) Mix 10 g of citric acid and 10 g of NaHCO3 (500 mesh) and stir for 30 min to obtain a mixture; 2) According to weight, 5 parts of the mixture in step 1) and 5 parts of 4,4'-oxybisbenzenesulfonylhydrazide are mixed to prepare a blowing agent, which is marked as blowing agent G.
[0042] Comparative Examples 5 to 9 The NaHCO3 (500 mesh) used in Example 1 was replaced by NaHCO3 (100 mesh), NaHCO3 (200 mesh), NaHCO3 (300 mesh), and NaHCO3 (400 mesh), respectively. The other operations were the same as in Example 1 to obtain blowing agents H, I, J, and K.
[0043] Application Examples The preparation steps of an EPDM rubber foam material are as follows: 1) According to weight, 100 parts of EPDM, 6 parts of carbon black, 40 parts of light calcium carbonate, 10 parts of zinc oxide, 1 part of lubricant, 2 parts of stearic acid and 7.5 parts of paraffin oil were added into a mixer, mixed at 100°C for 10 min to make the materials uniformly dispersed, and then thinly sliced at 50°C to obtain a first-stage rubber compound with a thickness of 2 mm; 2) Add the first-stage rubber material, 1.5 parts of accelerator, 1 part of vulcanizing agent, the remaining paraffin oil and 10 parts of the foaming agent prepared in the embodiment or comparative example into a mixer, and mix them for a second time at 60° C. for 5 min. After the materials are mixed evenly, thin sheets are formed at 80° C. to obtain a mixed rubber material with a thickness of 3 mm; 3) The mixed rubber material was extruded at 100°C, vulcanized at 130°C for 20 min, and vulcanized at 150°C for 10 min to finally obtain the EPDM rubber foam material.
[0044] Table 1 Comparison of properties of EPDM rubber foam materials prepared using the blowing agents of the examples and comparative examples
[0045] As can be seen from Table 1, the EPDM foam material incorporating PVA / SiO2 composite wrapped citric acid-sodium bicarbonate is significantly superior to the EPDM foam material prepared by the traditional OBSH foaming agent in terms of mechanical properties such as tensile strength, tear strength and elongation at break (Comparative Example 1). At the same time, it can be seen from Examples 1 to 3 that with the increase of the content of modified sodium bicarbonate in the foaming agent, the shrinkage rate of the EPDM foam material gradually increases. In order to ensure the dimensional stability of the EPDM foam material, the shrinkage rate of the material should be controlled at about 10%, and the tensile strength of the EPDM foam material prepared at this time is as high as 1130kPa, which is about 55% higher than the tensile strength of the OBSH foamed EPDM foam material of 730kPa, and the tear strength is increased by about 24%, which can ensure the stability and optimization of other properties. In addition, by comparing the EPDM foam material prepared by using sodium bicarbonate of different particle sizes (100-500 mesh), it can be seen that with the decrease of particle size, the mechanical properties of the material are improved and the pore structure is more stable.
[0046] Table 2 Test results of EPDM foamed materials prepared using the foaming agent of Example 1
[0047] The data in Table 2 further verify that the EPDM foam material prepared using the foaming agent of Example 1 has reached the lowest level in terms of environmental protection indicators such as odor, VOC (volatile organic compound) emissions and atomization value, has better environmental protection performance, and can meet more stringent environmental protection and low pollution requirements.
[0048] In summary, the present invention provides an EPDM foam material that has environmental friendliness, high mechanical properties, good dimensional stability and excellent pore structure, which is suitable for high-performance applications such as automotive seals, rail transit sealing pads, industrial shock-absorbing materials, etc., and has broad industrial application prospects.
[0049] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A low-odor, high-mechanical-performance EPDM rubber foam material, characterized in that: In parts by weight, the raw materials used include: 100 parts of EPDM rubber, 6 parts of carbon black, 40 parts of light calcium carbonate, 15 parts of paraffin oil, 10 parts of zinc oxide, 1 part of vulcanizing agent, 1.5 parts of accelerator, 2 parts of stearic acid, 1 part of lubricant, and 10 parts of foaming agent.
2. The EPDM rubber foam material according to claim 1, characterized in that: The vulcanizing agent includes any one of sulfur, zinc dibenzyl dithiocarbamate, dibenzoyl peroxide and dicumyl peroxide.
3. The EPDM rubber foam material according to claim 1, characterized in that: The accelerator includes at least one of zinc dibenzyl dithiocarbamate and tetrabenzyl thiuram disulfide.
4. The EPDM rubber foam material according to claim 1, characterized in that: The foaming agent is a mixture of 4,4'-oxybisbenzenesulfonyl hydrazide and modified sodium bicarbonate, and the mass ratio of the two is 1:(1-3).
5. The EPDM rubber foam material according to claim 4, characterized in that: The preparation method of the modified sodium bicarbonate comprises the following steps: (a) 5 g of PVA was dissolved in 100 mL of water, heated to 80 °C, stirred for 2 h, then 10 g of citric acid was added, stirred evenly, and then 10 g of NaHCO3 was slowly added, stirred continuously for 30 min, and then dried at 80 °C to obtain PVA-coated citric acid-NaHCO3 particles; (b) 2 g of SiO2 nanopowder was dispersed in 50 mL of 50% ethanol solution, and ultrasonicated for 30 min. Then, the PVA-coated citric acid-NaHCO3 particles prepared in step (a) were added, stirred for 1 h, and then centrifuged at 8000 rpm for 10 min. The particles were collected and dried. (c) Take 1 g of KH-550 and add it to 100 mL of anhydrous ethanol, stir evenly, add the particles prepared in step (b), make them evenly dispersed in the solution, stir at room temperature for 1 hour, and then dry at 50°C for 12 hours to obtain; Among them, the NaHCO3 used is 100 mesh ~ 500 mesh.
6. A method for preparing an EPDM rubber foam material as claimed in claim 1, characterized in that: The following steps are involved: 1) Add EPDM rubber, carbon black, light calcium carbonate, zinc oxide, lubricant, stearic acid and half of the paraffin oil into a mixer for mixing once to make the materials evenly dispersed, and then thinly slice to obtain the first stage rubber compound; 2) Add the first-stage rubber material, accelerator, vulcanizer, foaming agent and remaining paraffin oil into a mixer for secondary mixing, so that the materials are mixed evenly and then thinly sliced to obtain a mixed rubber material; 3) The mixed rubber material is sequentially subjected to extrusion, primary vulcanization, and secondary vulcanization to finally obtain the EPDM rubber foam material.
7. The method for preparing the EPDM rubber foam material according to claim 6, characterized in that: The temperature of the first mixing in step 1) is 90-110° C. and the time is 10-12 min.
8. The method for preparing the EPDM rubber foam material according to claim 6, characterized in that: Step 2) The secondary mixing is performed at a temperature of 60-90°C for 2-5 min.
9. The method for preparing the EPDM rubber foam material according to claim 6, characterized in that: Step 3) The extrusion temperature is 100-120°C.
10. The method for preparing the EPDM rubber foam material according to claim 6, characterized in that: Step 3) The primary vulcanization temperature is 130-135°C, and the time is 20-30 min; the secondary vulcanization temperature is 150-155°C, and the time is 10-30 min.
Citation Information
Patent Citations
Foaming agent, PVC foaming composition prepared from foaming agent and preparation method of PVC foaming composition
CN112679784A
Modified sodium bicarbonate foaming agent and preparation method thereof
CN119219962A
Damping products made from foamed rubber, and production method
CN1760253A
Rubber based flame-retardant foaming composition and its foamed product
JP2001288292A
Device for repairing a semiconductor light emitting device for a pixel and a repair method using the same
KR1020230064582A